Relationship between life-time exposure to ambient fine particulate matter and carotid artery intima-media thickness in Australian children aged 11-12 years - Guo, Yue Leon; Ampon, Rosario; Hanigan, Ivan; Knibbs, Luke; Geromboux, Christy; Su, Ta-Chen; Negishi, Kazuaki; Poulos, Leanne; Morgan, Geoffrey; Marks, Guy; Jalaludin, Bin (My University, 2021)
Long-term exposure to air pollutants, especially particulates, in adulthood is related to cardiovascular diseases and vascular markers of atherosclerosis. However, whether vascular changes in children is related to exposure to air pollutants remains unknown. This study examined whether childhood exposure to air pollutants was related to a marker of cardiovascular risk, carotid intima-media thickness (CIMT) in children aged 11-12 years old. Longitudinal Study of Australian Children (LSAC) recruited parents and their children born in 2003-4. Among the participants, CheckPoint examination was conducted when the children were 11-12 years old. Ultrasound of the right carotid artery was performed using standardized protocols. Average and maximum far-wall CIMT, carotid artery distensibility, and elasticity were quantified using semiautomated software. Annual and life-time exposure to air pollutants was estimated using satellite-based land-use regression by residential postcodes. A total of 1063 children (50.4% girls) with CIMT data, serum cholesterol, and modeled estimates of NO2 and PM2.5 exposure for the period 2003 to 2015 were included. The average and maximum CIMT, carotid distensibility, and elasticity were 497 μm (standard deviation, SD 58), 580 μm (SD 44), 17.4% (SD 3.2), and 0.48%/mmHg (SD 0.09), respectively. The life-time average concentrations of PM2.5 and NO2 were 6.4 μg/m3 (SD 1.4) and 6.4 ppb (SD 2.4), respectively. Both average and maximum CIMT were significantly associated with average ambient PM2.5 concentration (average CIMT: +5.5 μm per μg/m3, 95% confidence interval, CI 2.4 to 8.5, and maximum CIMT: +4.9 μm per μg/m3, CI 2.3 to 7.6), estimated using linear regression, adjusting for potential confounders. CIMT was not significantly related to NO2 exposure. Carotid artery diameter, distensibility, and elasticity were not significantly associated with air pollutants. We conclude that life-time exposure to low levels of PM2.5 in children might have measurable adverse impacts on vascular structure by age 11-12 years.
Environmental Pollution
Keywords: Adolescents and youth; Childhood and child development; Health and wellbeing; Surveys and survey methodology